IoT-based BIM integrated model for energy and water management in smart homes - Mervin Ealiyas, Mathews; Anandu E., Shaji; N., Anand; A. Diana, Andrushia; Siew Choo, Chin; Eva, Lubloy (Elsevier, 2023)
Increasing urbanization and growth in infrastructure create a demand to utilize modern tools to manage human needs. Effective integration of the Internet of Things (IoT) into the design of smart homes is an actively growing area in the construction industry. The ever-increasing demand and cost of energy require a smart solution in the design stage by the construction industry. It is possible to reduce household energy consumption by utilizing energy-efficient sustainable materials in infrastructure construction. Building Information Modeling (BIM) can provide a solution to effectively manage energy. The integration of the IoT further improves the design of comfortable smart homes by utilizing natural lighting. BIM aids in determining energy efficiency and making decisions by presenting the user with several design options via the 6D method. The present study considered a sample home design following the National Building Code (NBC) and American Society of Heating, Refrigerating, and Air Conditioning Engineers (ASHRAE) standards for implementation. Natural lighting analysis is carried out with the tool Insight 360 to analyze the energy consumption of the building. Some of the outputs obtained from the analysis are wall-to-window ratio (WWR), window shades, design options for window glass, energy use intensity (EUI), and annual energy cost (AEC). The results of the outputs are compared to find the energy-efficient optimum natural lighting of the proposed building. The lesser EUI (16%–21%) and AEC (23%–28%) are identified with the utilization of low emissivity glass in window panels compared with other types of glass. The proposed IoT-based BIM integration model proves that the effective utilization of natural lighting reduces overall household energy consumption.